Translation, Cultural Adaptation, and Validation of the Arabic Version of the STRONGkids Nutrition Screening Tool in the Moroccan Pediatric Clinical Setting - Barouaca, Hassan (The North African Journal of Food and Nutrition Research, 2025)
Background: Malnutrition among hospitalized children is associated with adverse clinical outcomes and prolonged length of stay. Systematic nutritional screening upon admission is a recognized standard of care.  Aims: This study aimed to validate the Arabic version of the STRONGkids nutritional risk assessment tool within a Moroccan pediatric population. Methods: A single-center, observational longitudinal study was conducted at Moulay Ali Chrif Hospital, Errachidia City, Morocco between June 2019 and February 2020. The study enrolled 367 children under-five years of age (337 for the validity analysis and 30 for the reliability analysis). The STRONGkids tool was translated into Arabic and administered upon hospital admission. The weight-for-height index served as the gold standard for assessing acute malnutrition. Diagnostic accuracy was evaluated employing the area under the receiver operating characteristic curve (AUROC), sensitivity, specificity, and predictive values. Agreement with the gold standard was assessed via Cohen’s Kappa coefficient.Results: Interobserver reliability indicated substantial agreement (κ=0.67). The STRONGkids tool demonstrated substantial agreement with the weight-for-height z-score (κ=0.61) and body mass index z-score (κ=0.67). The tool exhibited high diagnostic accuracy for screening a weight-for-height z-score below -2 SD (AUROC=0.94), with a sensitivity of 92.68% and a specificity of 88.51%. For predicting a hospital stay of ≥ 7 days and weight loss > 2%, the accuracy measures were AUROC = 0.59 and AUROC = 0.87 respectively.Conclusions: The Arabic adaptation of the STRONGkids instrument demonstrated robust concurrent validity and substantial interobserver reliability. While the tool exhibited limited predictive validity regarding the duration of hospitalization, it remains reliable metric for malnutrition risk screening among pediatric populations in Arabic-speaking countries.Keywords: Nutritional risk screening; Children; Translation; Validation; STRONGkids Arabic version.
Keywords: Nutritional risk screening; Children; Translation; Validation; STRONGkids Arabic version